Molecular dependencies and genomic consequences of a global DNA damage tolerance defect - Groot, Daniel De; Spanjaard, Aldo; Shah, Ronak; Kreft, Maaike; Morris, Ben; Cor Lieftink Sr; Joyce Ji Catsman; Ormel, Shirley; Ayidah, Matilda; Pilzecker, Bas; Buoninfante, Olimpia Alessandra; Paul Cm Van Denberk; et al. (bioRxiv, 2023)
DNA damage tolerance (DDT) enables replication to continue in the presence of fork stalling lesions. To determine the molecular and genomic impact of a global DDT defect, we studied PcnaK164R/-;Rev1-/- compound mutants. Double mutant (DM) cells displayed increased replication stress, hypersensitivity to genotoxic agents, replication speed, and repriming. A whole genome CRISPR-Cas9 screen revealed a strict reliance of DM cells on the CST complex, where CST promotes fork stability. Whole genome sequencing indicated that this DM DDT defect favors the generation of large, replication-stress inducible deletions of 0.4-4.0kbp, defined as type 3 deletions. Junction break sites of these deletions revealed preferential microhomology preferences of 1-2 base pairs, differing from the smaller type 1 and type 2 deletions. These differential characteristics suggest the existence of molecularly distinct deletion pathways. Type 3 deletions are abundant in human tumors, can dominate the deletion landscape and are associated with DNA damage response status and treatment modality. Our data highlight the essential contribution of the DDT system to genome maintenance and type 3 deletions as mutational signature of replication stress. The unique characteristics of type 3 deletions implicate the existence of a novel deletion pathway in mice and humans that is counteracted by DDT.Competing Interest StatementThe authors have declared no competing interest.Footnotes* Corrected some typographical errors and improved layout.